(untitled) (Kerala Journal of Psychiatry, 2016)
Neuroleptic Malignant Syndrome (NMS) is an idiosyncratic, fatal complication of antipsychotic treatment. We report the case of a 37-year-old woman who was on medications for cardiac problems and presented with acute onset of manic symptoms of four days duration. She was admitted due to presence of altered sensorium. Hypokalemia was detected. She was started on Tab. Risperidone and intramuscular Haloperidol for her behavioral problems. However, the delirium worsened and she developed rigidity. Investigations revealed elevated creatinine phosphokinase (CPK) and worsening hypokalemia. In view of muscular rigidity, elevated CPK and worsening delirium even after correcting hypokalemia, a diagnosis of NMS was considered. Her symptoms improved once Risperidone and Haloperidol were stopped and treatment for NMS was instituted. This case demonstrates that early or impending NMS can have atypical presentations, pose a diagnostic dilemma and delay treatment; and highlights the importance of early diagnosis and treatment of NMS.